The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.12998/wjcc.v10.i32.11804
|View full text |Cite
|
Sign up to set email alerts
|

T-cell immunoglobulin mucin molecule-3, transformation growth factor β, and chemokine-12 and the prognostic status of diffuse large B-cell lymphoma

Abstract: BACKGROUND The effects of T-cell immunoglobulin mucin molecule-3 (Tim-3), transforming growth factor β (TGF-β), and chemokine-12 (CXCL12) expression on the prognosis of patients with diffuse large B-cell lymphoma (DLBCL) have not been elucidated. AIM To examine the correlation between Tim-3, TGF-β and CXCL12 expression and DLBCL prognosis. METHODS Lymph node tissues of 97 patients with DLBCL and 93 normal-response hyperplastic lymph node tiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Furthermore, galectin-9 knockout mice are more resistant to AML morbidity/mortality while double blockade of PD-1/PD-L1 and TIM-3/galectin-9 as associated with reduced leukemic burden ( 111 ). TIM-3 expression has also been found to correlate to poor prognosis in other hematologic malignancies such as DLBCL, ALL, MDS, Chronic Myelogenous Leukemia (CML), and Chronic Myelomonocytic Leukemia (CMML) ( 112 115 ). Thus blockade of TIM-3/galectin-9 is a potentially effective target for further treatment in several hematologic malignancies.…”
Section: Other Targetable Checkpoint Moleculesmentioning
confidence: 99%
“…Furthermore, galectin-9 knockout mice are more resistant to AML morbidity/mortality while double blockade of PD-1/PD-L1 and TIM-3/galectin-9 as associated with reduced leukemic burden ( 111 ). TIM-3 expression has also been found to correlate to poor prognosis in other hematologic malignancies such as DLBCL, ALL, MDS, Chronic Myelogenous Leukemia (CML), and Chronic Myelomonocytic Leukemia (CMML) ( 112 115 ). Thus blockade of TIM-3/galectin-9 is a potentially effective target for further treatment in several hematologic malignancies.…”
Section: Other Targetable Checkpoint Moleculesmentioning
confidence: 99%
“…In many tumors such as melanoma [ 17 ] and gastric cancer [ 18 ], the increase of TIM3 is associated with poor prognosis and CD8 + TILs exhaustion. Nevertheless, there are contradictory conclusions about the effect of TIM3 expression on the prognosis of DLBCL patients [ 3 , 6 , 13 , 19 , 20 ]. Previous studies demonstrated that the increase of TIM3 may be related to CD8 + TILs exhaustion and immune deficiency in DLBCL [ 13 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Prognostic biomarkers provide basic information for predicting treatment outcomes and survival and therefore play a vital role in achieving reliable and accurate treatment predictions. Currently, CD97B mutation, CD30 expression and T-cell immunoglobulin mucin molecule-3 (Tim-3) expression have been confirmed as prognostic biomarkers of DLBCL ( 3 ), but these indicators are not widely used clinically due to technical limitations or difficulty in obtaining them ( 4 , 5 ). Hence, there is a need for prognostic clinical markers that are cost-effective, simple, and readily available.…”
Section: Introductionmentioning
confidence: 99%